NOVEL SATYANING ATI (TINJAUAN SOSIOLOGI SASTRA) - Ni Wayan Apriani (Subasita: Jurnal Sastra Agama dan Pendidikan Bahasa Bali, 2021)
This study aims to determine the narrative structure and social problems in the novel Satyaning Ati. The data in this study were sourced from the novel Satyaning Ati by I Komang Alit Juliartha which was collected using reading, observing, copying and collecting techniques according to the required classification. After the data were collected, the data were analyzed using qualitative descriptive techniques. The result of this research is that the novel Satyaning Ati is composed of a narrative structure including a synopsis, theme, character and characterization, plot, setting and message. The social problems contained in the novel include poverty, family disharmony, social inequality, homosexuality and environmental pollution. Hopefully, through this research, the government will be more sensitive and able to find solutions to social problems that are reflected in the novels that are real in the field.Keywords: novel of Satyaning Ati, sociology of literature